Evaluation of the Shadow Economy and Informal Employment Trends in Lithuania - Pocius, Arūnas (Lithuanian Journal of Statistics, 2019)
The author analyses the state of the shadow economy, informal employment and their trends based on differentstatistical calculation methodologies and survey data. The evaluation of the situation in Lithuania is based on the data of StatisticsLithuania, State Social Insurance Fund Board (SODRA), special surveys and results of statistical calculations. According to researchexperience, the methodological issues of evaluation of informal employment are discussed. Assiduous attention is paid to theevaluation and the scope of the shadow economy and the comparative analysis of informal employment issues in the EU. Whileassessing the trends in the shadow economy, the indicators from the research of different authors or institutions are compared usingdifferent calculation methods – to determine relative trends in the shadow economy.
Keywords: economy; labour market; informal employment; illegal employment; labour taxation